Factors that affecting customer loyalty towards airlines industry - Devaisuwaran, Puvaneswary; Sapuan, Nursuhaida; Balanting, Rezet; Qasim, Muhammad (2015)
Airlines Industries are making attempt to construct long lasting relationship towards the consumers and critically retain the aviation loyalty. Maintaining of precious consumers is the important part of the airline services to obtain the level of competitive superiority. Thus, the purpose of this research is to examine the exploratory factors that affecting customer loyalty towards airline industry. The main four factors which are influencing consumer loyalty towards airline industry are perceived value, perceived quality, safety and customer satisfaction. Therefore, the aim of this study is to identify the exploratory factors which affecting customer loyalty towards airline industry. A quantitative research was carried out in order to accomplish this research. A set of questionnaire was developed and conveniently distributed to 150 respondents among University Malaysia Kelantan and University Science Malaysia students. Descriptive Analysis, Reliability Test and Pearson correlation was being used to analyze the data. Based on this research, it shows that there are relationship between the perceived value, perceived quality, safety and customer satisfaction with customer loyalty towards airlines industry